Influence Of Capital Structure, Profitability, Tax Planning And Expensesdeferred Tax On Corporate Income Tax On Various Industrial Sector Companies Listed On The Indonesian Stock Exchange 2018 – 2022 - Latersia Br Gurusinga; Jhon Raphael Saragih; Juli Anna (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to determine and analyze the extent of the influence of Capital Structure, Profitability, Tax Planning and Deferred Tax Expenses on Corporate Income Tax in companies in various industrial sectors. The data collection technique used is secondary data in the form of annual reports for the 2018-2022 period on companies in various industrial sectors. The sample in this study was taken from the financial reports of companies in various industrial sectors listed on the Indonesia Stock Exchange in 2018-2022 so that the data obtained was 24 companies x 5 years = 120 data. The data will be analyzed using quantitative methods. The results of the research show that Capital Structure, Profitability, Tax Planning and Deferred Tax Expenses have a significant and significant effect on Corporate Income Tax and only the Tax Planning variable has a positive effect on Corporate Income Tax in various industrial sector companies while the other variables have a negative effect on Corporate Income Tax in companies various industrial sectors.